Plastic Particles in Silverside (Stolephorusheterolobus) Collected at Paotere Fish Market, Makassar - Akbar Tahir; Chelsea M. Rochman (Hasanuddin University, 2014)
Plastics represent the latest contaminant in the marine environment. Although plastics without doubt represent a uniquely valuable material particularly in construction, packaging and fishing gear applications. Current research on plastic debris in digestive tract content of pelagic fish is part of ongoing collaboration between University of Hasanuddin and University of California at Davis. Locally caught and consumed Silverside (Stolephorusheterolobus) or widely known as anchovies has been the subject on this studies. Freshly landed fish were collected from Paotere fish market, which is also the biggest fish wholesale location at Makassar City, South Sulawesi, Indonesia. At laboratory fish digestive tracts were removed and digested in 10% KOH at 60o C overnight, followed with plastic particles observation using binocular microscope. Four out of 10 fish investigated were found to contained plastic particles in their digestive tract. This is the first work on plastic debris in fish gut ever conducted in the region, which is in accordance to previous works on plastics debris elsewhere and will be further discussed for their possible effects, both on food safety and human toxicology.